2019
DOI: 10.1186/s40478-019-0766-7
|View full text |Cite
|
Sign up to set email alerts
|

Complement-independent bystander injury in AQP4-IgG seropositive neuromyelitis optica produced by antibody-dependent cellular cytotoxicity

Abstract: Cellular injury in AQP4-IgG seropositive neuromyelitis spectrum disorder (herein called NMO) involves AQP4-IgG binding to astrocytes, resulting in astrocyte injury by complement-dependent cytotoxicity (CDC) and antibody-dependent cellular cytotoxicity (ADCC) mechanisms. The rapid disease progression, severe tissue damage, and abundant leukocyte infiltration seen in some NMO patients suggest a more direct mechanism for demyelination and neurologic deficit than secondary injury from astrocyte loss. Here, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 69 publications
0
34
0
1
Order By: Relevance
“…In line with this research, our univariate analysis also found that age of onset was positively associated with outcomes in first-attacked NMOSD patients. AQP4-IgG was a specific biomarker for the diagnosis of NMO, which can cause demyelination and neurologic deficit by binding to astrocytes and leading to astrocyte injury (41). Positive AQP4 status was closely related to rapid progress, severe tissue damage, and abundant infiltration of leukocyte in some NMO patients (42).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this research, our univariate analysis also found that age of onset was positively associated with outcomes in first-attacked NMOSD patients. AQP4-IgG was a specific biomarker for the diagnosis of NMO, which can cause demyelination and neurologic deficit by binding to astrocytes and leading to astrocyte injury (41). Positive AQP4 status was closely related to rapid progress, severe tissue damage, and abundant infiltration of leukocyte in some NMO patients (42).…”
Section: Discussionmentioning
confidence: 99%
“…3 AQP4-IgG binding to astrocytic AQP4 leads to classical complement cascade activation and granulocyte and lymphocyte infiltration that combine to damage neural tissues. 4,5 IL-6 may drive disease activity in NMOSD by promoting plasmablast survival, stimulating AQP4-IgG secretion, reducing blood-brain barrier (BBB) integrity and functionality, and enhancing proinflammatory T-lymphocyte differentiation and activation (figure A). CSF and serum IL-6 levels are significantly elevated in patients with NMOSD, and IL-6 inhibition has been shown to improve disease control (table 1).…”
mentioning
confidence: 99%
“… 3 AQP4-IgG binding to astrocytic AQP4 leads to classical complement cascade activation and granulocyte and lymphocyte infiltration that combine to damage neural tissues. 4 , 5 …”
mentioning
confidence: 99%
“…These findings, taken together with the observation of a penumbra lesion in rats as mentioned above , support a role for ADCC in NMO pathogenesis and suggested ADCC as a potential therapeutic target. In a follow‐on study, in vivo evidence was reported for an “ADCC bystander” mechanism of killing involving leukocyte activation by astrocyte‐bound AQP4‐IgG and killing of nearby cells (Figure B) .…”
Section: Scientific Advances Utilizing Nmo Animal Modelsmentioning
confidence: 90%